Rethinking inequality under autocracy: Parties, citizens, and preferences - Lott, Lars (2021)
The causes of different levels of political and economic inequalities and related public policies under autocratic regimes are diverse. Existing works are mainly concerned with questions such as how political institutions matter for policy outcomes under authoritarianism and how citizens under autocratic rule adopt political and economic preferences conditioned by the nature of the regime environment. However, the literature still lacks a framework that systematically theorizes and empirically compares the effects of different institutional designs of dictatorships on policies that affect economic and political inequalities, such as redistribution and women's political inclusion. In addition, the consequences of political and economic inequality under authoritarianism for ordinary citizens are particularly important but are still understudied. The present dissertation seeks to answer whether and how the institutional foundations of autocracies determine economic and political inequalities and whether and how these inequalities affect ordinary citizens in the short and long term. The main argument at the heart of this dissertation is that autocratic institutions, and especially the strength of an incumbent's party, matter for redistributive policies and inequalities and their consequences for ordinary citizens. The four research papers that form the core of this dissertation employ quantitative methods with cross-national data on redistribution and women's political inclusion and individual-level data across countries on political participation and redistributive preferences. A crucial goal of this doctoral thesis is to propose a theoretical framework explaining public policies that address political and economic inequalities and the attitudinal effects of those policies and inequalities on ordinary citizens. The focus of my first dissertation paper is on theorizing and empirically examining variation in income redistribution across autocracies. It argues that the degree of electoral uncertainty affects two mechanisms that shape the redistributive nature of autocratic regimes. The inclusion and exclusion from political power on the grounds of socioeconomic and social attributes and the institutionalization of political parties determine autocrats' incentive and capacity for redistributing income and economic benefits. First, the empirical analysis suggests that more inclusionary ruling coalitions correspond with higher levels of income redistribution compared to more exclusionary regimes. Second, regimes with higher levels of party institutionalization redistribute more than regimes in which authoritarian parties are less institutionalized. However, third, the effects are largely conditional on electoral uncertainty. The second paper of this dissertation examines the association between women's political inclusion and incumbent party strength in authoritarian regimes and thereby investigates policies that autocratic regimes implemented to reduce this form of horizontal inequality. This article argues that the degree of party institutionalization is the main determinant of women's political inclusion under authoritarian rule. Similar to the first paper, it argues that institutionalized party rule determines authoritarian parties' incentive and capacity for introducing more gender-equal political processes and political outputs. Although previous research stressed the link between authoritarian regime types and gender equality, this study finds regime types explain little of the variation in gender equality. In contrast, regimes with higher levels of party institutionalization provide more gender-equal politics and policies than regimes in which authoritarian parties are less institutionalized. The third paper focuses on individuals living in autocratic regimes and their political participation. Thus, similar to the fourth paper, it shifts the level of inquiry to the individual level. The third paper investigates the following questions. What effect does economic inequality in authoritarian regimes have on the political participation of their citizens? Do individual income and repression each have a greater effect than economic inequality? The paper benefits from three prominent theories, namely the Conflict, Relative Power, and Resource Theories that address the inequality-participation puzzle in democracies. However, theoretical arguments and empirical evidence regarding non-democratic regimes are scarce. Thus, the third paper argues that it is individual income and the level of repression rather than economic inequality that explain political participation in autocracies. The paper demonstrates that higher levels of economic inequality hardly suppress political participation among citizens in general. However, individual income has a more powerful effect on civil society participation, while the level of repression decreases the likelihood of voting more strongly than income. The fourth paper sheds light on how authoritarian regimes have a lasting imprint on their citizens' ideas and values in the long term and on which mechanisms determine the redistributive preferences of their former citizens. It is widely established that autocracies attempt to indoctrinate their citizens to have compliant subjects. However, the long-term consequences of socialization under authoritarian rule are weakly conceptualized, and empirical evidence is rare, especially regarding citizens' economic preferences. The fourth paper proposes a distinction between three different mechanisms: state repression, political indoctrination, and exposure to autocracies during citizens' lifetimes. It finds that socialization under a highly indoctrinating regime leaves a strong pro-redistributive legacy, while highly repressive regimes also leave a pro-redistributive legacy. This study contributes to our understanding of how state repression and indoctrination affect ordinary citizens in the long term. This dissertation underlines the finding that highly institutionalized dictatorships provide public policies that address political and economic inequalities, while ordinary citizens are also affected by economic and political inequalities under autocratic rule. This doctoral thesis complements existing research on the causes and consequences of inequality under autocracy, socialization under authoritarianism, and citizens' preference formation in autocratic environments.
Keywords: Hochschulschrift